Tumor Size and Diabetes Are the Most Important Pre-Operative Prognostic Factors Influencing Survival After Pancreaticoduodenectomy in Pancreas Cancer Patients - Del Chiaro, Marco; Rangelova, Elena; Ansorge, Christoph; Blomberg, John; Segersvärd, Ralf (JOP. Journal of the Pancreas, 2012)
Context The median survival in resected pancreatic ductal adenocarcinoma (PDAC) is about two years. However, a considerable percentage of patients die within the first year after resection. Objective The aim of this study was to evaluate pre-operative factors predicting a short survival after pancreaticoduodenectomy (PD) for PDAC. Methods One hundred consecutive patients undergone PD for PDAC without in-hospital mortality from October 2006 to July 2010 were retrieved from our prospective database. The cohort was divided by survival into short term (≤12 months: group A) and long term (>12 months: group B) survivors and evaluated regarding pre-operative factors including age, weight loss, BMI, tumor size and proximity (no contact-contact) to the portal/mesenteric vein (PV/SMV). Results No significant differences were found between group A (n=27) and group B (n=73) regarding mean age (68±2 vs. 66±1 years; P=0.3), weight loss (87% vs. 85%; P=1.0), BMI (24±0.6 kg/m2 vs. 24±0.5 kg/m2; P=0.7) or adjuvant treatment. Group A had bigger tumors (35±2 mm vs. 29±1 mm; P=0.01) but no significant difference in proximity of the tumor to the PV/SMV (contact: A 67% vs. B 49%; P=0.2) or venous resections. Group A had more frequently pre-operative diabetes (33% vs. 9.6%; P=0.01) compared to group B. Conclusion Tumor size and pre-operative diabetes seems to be important negative prognostic factors for survival after PD for PDAC.